Psychological Distress And The Sleep Quality In Older Patients With Chronic Disease - Yodang Yodang; Akbar Harisa; Syahrul Syahrul (Poltekkes Kemenkes Surakarta, 2021)
Background: The prevalence of chronic disease in elderly increase year by year worldwide and it’s related to mortality and decrease of quality of life. The majority of elderly patients complaints about sleep disorders and that affects sleep quality, health status and quality of life. Psychological aspect was identified as one main contributor in sleep disorders among elderly who suffer from chronic disease. This study aims to determine the effect of psychological distress on sleep quality among elderly patients with chronic disease. Methods: This study applied a quantitative research design with cross-sectional approach. The study conducted in a teaching university hospital from October to November 2021. Population is elderly with chronic diseases, the participants selected by using total sampling method. Data collection using psychological distress related questionnaire and Pittsburg Sleep Quality Index (PSQI). Data analysis applied Fishers’ Exact test. Results: There are 52 older patients participate in this study. The study finding 85.6% participants have psychological distress and 51.9% have poor quality of sleep. Based on Fishers’ Exact test analysis, the p-value was 0.308 (statistically insignificant). Conclusion: This study finding report that psychological distress statistically has no significant affect on sleep quality among elder patients who suffer from chronic disease. However, some participants have poor sleep quality. Study in advance to investigate how psychological status affect sleep quality is needed.